Analisis Responsiveness & Action KAI Access untuk Meningkatkan Loyalitas Pengguna - Wahyono, Agatha Christy; Zaizatun Nisa (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Technological developments have penetrated various sectors of life, including in the transportation and communication lines in Indonesia. KAI Access is a digital service issued by PT Kereta Api Indonesia in the form of an application. This application is present as a strategic innovation to improve the convenience and comfort of customers in accessing various train services, from ticket bookings, schedule information, to cancellations and refunds. However, from the complaint data submitted by customers, there are two biggest problems that are often experienced, namely related to responsiveness and action from KAI Access which is considered slow in handling user complaints and technical problems. When quick response services are not accompanied by concrete settlement actions, customer trust tends to decline. This research is based on service theory with a service quality and excellent service approach, where the variables of responsiveness and action are the main focus in the analysis of customer loyalty. Using a quantitative approach, with data collection techniques in the form of questionnaires, interviews, and literature studies, the respondents in this study were KAI Access users from the Edan Sepur train loving community. The results showed that the action variable had a positive and significant influence on customer loyalty, while the responsiveness variable did not have a significant influence directly. An important conclusion from this study is that in the context of digital applications such as KAI Access, customers prioritize concrete problem solving rather than just quick response. Therefore, PT KAI needs to strengthen concrete actions in handling complaints to increase long-term loyalty. Therefore, PT KAI needs to strengthen concrete actions in handling complaints to increase long-term loyalty, especially in the era of digitalization of public services that continues to grow rapidly.